The Effects of Contract Detail and Prior Ties on Contract Change: A Learning Perspective - Xing, Zhe (Adele); Mayer, Kyle J.; Xie, Xuanli; Reuer, Jeffrey J.; Klijn, Elko (Organization Science, 2021)
Despite the large literature on alliance contract design, we know little about how transacting parties change and amend their underlying contracts during the execution of strategic alliances. Drawing on existing research in the alliance contracting literature, we develop the empirical question of how contract detail and prior ties influence the amount, direction, and type of change in such agreements during the collaboration. We generated a sample of 115 joint ventures (JVs) by distributing a survey to JV board members or top managers and found that the amount of contract change is negatively associated with the level of detail in the initial contract but is positively associated with the number of prior ties between alliance partners. In relation to the direction of contract change, we find that the level of detail of the initial agreements negatively correlates with the likelihood of removing or weakening existing provisions and that prior collaborative experience positively correlates with the likelihood of strengthening of existing provisions or adding of new ones. We also find that prior ties affect the type of change in that JV parents prefer to change enforcement provisions more so than the coordination provisions in the contract. Our paper generates new insights on the complementarities between relational governance and transaction cost economics perspectives on alliance contracting.